DDIS-03. HARNESSING siRNA NANOMEDICINE FOR THERAPEUTIC GENE SILENCING IN GLIOBLASTOMA - Gutkin, Anna (Neuro Oncol, 2017)
GBM is the most common primary brain tumor in adults, with a very poor prognosis. Despite tremendous efforts to develop new drugs, the treatment of GBM remains a great challenge. The use of nanoparticles (NPs) has emerged as a potential strategy for diagnosis and treatment of tumors, GBM especially. The key advantage of utilizing NPs as delivery platform is the ability to tailor-made them to achieve both controlled drug release and tissue specificity. We validated this strategy by direct injection of NPs to the tumor site and by systemic administration. Novel hyaluronan (HA)-grafted lipid nanoparticles (LNPs), devised in our laboratory, can carry siRNAs and bind to a specific CD44 variants expressed on tumor cells. We examined the effect of LNPs treatment on human GBM cell lines and cultured samples of GBM patients. HA-LNPs loaded with siRNA against the gene PLK1 (siPLK1) can induce eﬀective cell death in vitro. We also have shown that by direct injection of HA-siPLK1- LNPs to the brains of tumor bearing mice did not only decreased the levels of expression of the gene but also prolonged the survival of the mice by 60%, the longest ever reported survival of mice in this orthotopic GBM model in nude mice. Next, we have established a new model in our lab by injecting mouse glioma stem cells (GSCs) into a normal C57Bl/6 mice that resembles the characteristics of a human tumor. Using an in vivo fluorescent imaging system and confocal microscopy, we have shown that by systemic injection, HA-LNPs can reach the brain and enter the GSCs specifically. Our results suggest that treatment with our nanoparticles based system can specifically and efficiently target GBM cells in-vitro and in-vivo. This HA-LNPs based platform could potentially mature to a clinical trial, and ultimately might become a new therapeutic modality in GBM.